2023
DOI: 10.1002/adsc.202300347
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of C‐3‐Functionalized Imidazo[1,2‐a]pyridines via Direct para‐Position Arylation of Electron‐Rich Anilines under Transition‐Metal‐Free Conditions

Abstract: A multicomponent tandem arylation reaction was established under transition‐metal‐free conditions to synthesize structurally diverse imidazo[1,2‐a]pyridines. As N,N‐dimethylaniline is not only a reactant but also a methylation reagent, its use affords an alternative route for methylation. This approach features mild reaction conditions and good functional group tolerance, providing 29 compounds in acceptable yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…((Phenylimidazo[1,2-a]pyridin-3-yl)methyl)aniline (4aa). 22,33 According to the general procedure, compound 4aa was prepared; TLC (R f ): (PE/EA = 60:40) 0.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…((Phenylimidazo[1,2-a]pyridin-3-yl)methyl)aniline (4aa). 22,33 According to the general procedure, compound 4aa was prepared; TLC (R f ): (PE/EA = 60:40) 0.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…21 The very same year Ji's group approached a multicomponent tandem arylation reaction under transition-metal-free conditions (Scheme 1c). 22 Paturea et al in 2022 revealed an electrochemical system for amino methylation of imidazopyridine (Scheme 1d). In all of the cases, the substrate scope of N,N-dialkyl anilines was limited to para-substituted N,N-dimethylanilines.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation